On-farm welfare assessment of dairy cattle by animal-linked parameters in Bangladesh - Ahsan, Shamir; Islam, M Ariful; Islam, Md Taohidul (Research in Agriculture Livestock and Fisheries, 2016)
The present study was conducted in 33 dairy farms to evaluate the welfare quality of Australian-zebu cross bred cows through some animal-based welfare indicators. The main aims of this research were to identify welfare issues facing dairy cows and investigate whether indicators are associated with measures of welfare and performance efficiency. The assessment of animal welfare was performed (330 animals) Australian-cross breed in family dairy farms at Sirajganj district of Bangladesh. Data were collected through face-to-face interview with farmers, followed by an inspection and observation of dairy cows. A total 330 females (43 heifers and 287 cows) were included in this study. Body condition, body cleanliness, injury, lameness, health status and milk yield were assessed. Among studied animals, body condition score 2 about (65.5%), hock joint injury (83.6%), knee injury (48.8%), and a pronounced state of poor cleanliness on: dirty udder (55.9%), flank (55.0%) and hind limbs (96.4%) were observed. Health status including diarrhea, respiratory distress, coughing, nasal and ocular discharge were present in some animals. The results indicate that very good BCS and mastitis free cows are related to higher milk yields. Results of this study may indicate the some indicators that influence the animal welfare and productivity in selected farms. As this work was a preliminary study, so the comprehensive research is needed to further develop the prototype protocol. Res. Agric., Livest. Fish.3(3): 417-424, December 2016